2013
DOI: 10.1021/jp400412n
|View full text |Cite
|
Sign up to set email alerts
|

Branching Ratio Measurements for Vacuum Ultraviolet Photodissociation of 12C16O

Abstract: ABSTRACT:The branching ratios for the spin-forbidden photodissociation channels of 12 C 16 O in the vacuum ultraviolet (VUV) photon energy region from 102 500 (12.709 eV) to 106 300 cm −1 (13.180 eV) have been investigated using the VUV laser time-slice velocity-map imaging photoion technique. The excitations to three 1 Σ + and six 1 Π Rydberg-type states, including the progression of W(3sσ) 1 Π(v′ = 0, 1, and 2) vibrational levels of CO, have been identified and investigated. The branching ratios for the prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 37 publications
4
48
0
Order By: Relevance
“…Laser-generated ultraviolet radiation is sometimes used in photoabsorption experiments and provides the highest spectral resolution (Gao et al 2013;Niu et al 2014), but generally cannot be tuned over a large wavelength range or provide controllable intensity. Special techniques are required to record ultraviolet photoabsorption spectra for wavelengths shorter than 105 nm due to the lack of transmitting material for use as windows or beam splitters.…”
Section: Experimental Cross Sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser-generated ultraviolet radiation is sometimes used in photoabsorption experiments and provides the highest spectral resolution (Gao et al 2013;Niu et al 2014), but generally cannot be tuned over a large wavelength range or provide controllable intensity. Special techniques are required to record ultraviolet photoabsorption spectra for wavelengths shorter than 105 nm due to the lack of transmitting material for use as windows or beam splitters.…”
Section: Experimental Cross Sectionsmentioning
confidence: 99%
“…Less commonly, experimenters count neutral photofragments (e.g., Morley et al 1992;Walter et al 1993;Gao et al 2013) or detect their fluorescence following dissociation into excited states (e.g., Lee 1984;Biehl et al 1994). The emission of photoexcited molecules has is sometimes recorded (e.g., Jonas et al 1990;Heays et al 2014a) and provides further information on the decay branching of excited states.…”
Section: Experimental Cross Sectionsmentioning
confidence: 99%
“…This state dissociates to ground-state C( 3 P) + O( 3 P) atoms, and has a principal electronic configuration differing from W 1 by only a single electron orbital. 42 Indeed, the product-sensitive photodissociation 12 C 16 O experiment of Gao et al 24 found a 75% probability that the J = 1 and 2 levels of W (1) dissociate to form ground state atoms, with the remainder dissociating as C( 1 D) + C( 3 P).…”
Section: Deperturbation Of Intensities and Widthsmentioning
confidence: 99%
“…The W (1) ← X(0) band, in particular, has been studied previously in absorption, [17][18][19][20][21][22][23] with most experiments focussing on 12 C 16 O. Further complications in the 12 C 16 O W (1) ← X(0) photodissociation spectrum were identified by Gao et al 24 by means of VUV laser excitation of CO and velocity discrimination of the atomic-C dissociation product. They determined that the lowest rotational levels of W (1) decay via two channels, yielding both C( 1 D) + O( 3 P) and C( 3 P) + O( 3 P) dissociation products.…”
Section: Introductionmentioning
confidence: 99%
“…THE JOURNAL OF CHEMICAL PHYSICS 145, 166102 (2016) Note: Calculation of the branching ratios for the predissociation of the Rydberg CO W 1 Π(v=1) level H. Lefebvre-Brion 1,a) and A. Kalemos 2,b) In our previous paper, 1 we have succeeded in reproducing the experimental predissociation width of the v = 1 level of the W 1 Π CO state, a Rydberg state that converges to A 2 Π of the CO + cationic system and observed by Heays et al 2 This has been accomplished by solving a system of seven coupled equations. The only problem to be solved was the calculation of the predissociation branching ratios observed by Gao et al 3 In order to evaluate the partial widths, Γ j , of the jth dissociation channel, we have employed the method due to Humblet and Rosenfeld. 4 We apply their formalism to the adiabatic nuclear wave functions ξ j which are written as…”
mentioning
confidence: 99%